2004
DOI: 10.1007/bf02344716
|View full text |Cite
|
Sign up to set email alerts
|

Nerve conduction block utilising high-frequency alternating current

Abstract: High-frequency alternating current (AC) waveforms have been shown to produce a quickly reversible nerve block in animal models, but the parameters and mechanism of this block are not well understood. A frog sciatic nerve/gastrocnemius muscle preparation was used to examine the parameters for nerve conduction block in vivo, and a computer simulation of the nerve membrane was used to identify the mechanism for block. The results indicated that a 100% block of motor activity can be accomplished with a variety of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
307
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 248 publications
(319 citation statements)
references
References 46 publications
10
307
2
Order By: Relevance
“…11). However, previous studies using animals (Bhadra et al, 2006;Bhadra and Kilgore, 2005;Bowman and McNeal, 1986;Kilgore and Bhadra, 2004;Rehoul and Rosenblueth, 1939;Rosenblueth and Rehoul, 1939;Tai et al, 2004;2005c;Tanner, 1962;Williamson and Andrews, 2005) showed that the minimal blocking frequency varied between 1 kHz and 10 kHz in different nerves of various species using different electrode geometries. Therefore, the temperature might be one of the factors that could influence the minimal blocking frequency.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…11). However, previous studies using animals (Bhadra et al, 2006;Bhadra and Kilgore, 2005;Bowman and McNeal, 1986;Kilgore and Bhadra, 2004;Rehoul and Rosenblueth, 1939;Rosenblueth and Rehoul, 1939;Tai et al, 2004;2005c;Tanner, 1962;Williamson and Andrews, 2005) showed that the minimal blocking frequency varied between 1 kHz and 10 kHz in different nerves of various species using different electrode geometries. Therefore, the temperature might be one of the factors that could influence the minimal blocking frequency.…”
Section: Discussionmentioning
confidence: 96%
“…The block of spontaneous neuronal activity was always coincident with a stimulus-induced rise in extracelluar potassium concentration, suggesting that a constant potassium outflow from the neurons was induced by the stimulation. The stimulation frequency to block the hippocampal neuron is relatively low (<500 Hz) compared to the minimal stimulation frequency required to block the axonal conduction (1-10 kHz) (Bhadra et al, 2006;Bhadra and Kilgore, 2005;Bowman and McNeal, 1986;Kilgore and Bhadra, 2004;Rehoul and Rosenblueth, 1939;Rosenblueth and Rehoul, 1939;Tai et al, 2004;2005c;Tanner, 1962;Williamson and Andrews, 2005). However, this frequency discrepancy might be caused by the slow membrane dynamics of the neuron and the longer duration action potential.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations